Analisis Framing Pemberitaan Konser Blackpink di Stadion Gelora Bung Karno dalam Media Liputan6.com dan Kompas.com ) - Ade Irma; Hendra Setiawan (Peneliti.net, 2023)
This study aims to find out how a media creates framing of the news it writes. The method used in this research is a qualitative-descriptive method. The subjects in this study were two online news media, namely Kompas.com and Liputan6.com with the object of research being one text of each news.